Prevalence of chromosomal abnormalities and Y chromosome microdeletion among men with severe semen abnormalities and its correlation with successful sperm retrieval - Mariano Mascarenhas; Sumi Thomas; Mohan S Kamath; Ramya Ramalingam; Ann Marie Kongari; S Yuvarani; Vivi M Srivastava; Korula George (Wolters Kluwer Medknow Publications, 2016)
AIM: To estimate the prevalence of chromosomal abnormalities and Y chromosome microdeletion among men with azoospermia and severe oligozoospermia and its correlation with successful surgical sperm retrieval. SETTING AND DESIGN: A prospective study in a tertiary level infertility unit. MATERIALS AND METHODS: In a prospective observation study, men with azoospermia and severe oligozoospermia (concentration <5 million/ml) attending the infertility center underwent genetic screening. Peripheral blood karyotype was done by Giemsa banding. Y chromosome microdeletion study was performed by a multiplex polymerase chain reaction. RESULTS: The study group consisted of 220 men, 133 of whom had azoospermia and 87 had severe oligozoospermia. Overall, 21/220 (9.5%) men had chromosomal abnormalities and 13/220 (5.9%) men had Y chromosome microdeletions. Chromosomal abnormalities were seen in 14.3% (19/133) of azoospermic men and Y chromosome microdeletions in 8.3% (11/133). Of the 87 men with severe oligozoospermia, chromosomal abnormalities and Y chromosome microdeletions were each seen in 2.3% (2/87). Testicular sperm aspiration was done in 13 men and was successful in only one, who had a deletion of azoospermia factor c. CONCLUSIONS: Our study found a fairly high prevalence of genetic abnormality in men with severe semen abnormalities and a correlation of genetic abnormalities with surgical sperm retrieval outcomes. These findings support the need for genetic screening of these men prior to embarking on surgical sperm retrieval and assisted reproductive technology intracytoplasmic sperm injection.